Electronic commerce: What is different in Germany? Keynote address, COTIM '99, Sept. 26, 1999, Providence, R.I., USA - Wolfgang Fritz (Technische Universität Braunschweig, Institut für Marketing, 1999)
According to a widespread 0plnlon, Germany is lagging behind. Many people in- and outside Germany believe that the Germans slumber through some of the most in1portant economic trends and technological developments, especially at the incipient stages. For example Coke, color television, and computers were not invented there, and Germans often regarded words like iMac or E-commerce as slips of the pen, or the term Internet simply as an abbreviation of the word “international”. But does this picture accurately portray today's reality of the Internet and E-commerce? In the following, I will present an outline of the current situation in Germany and Europe and of some important changes that can be expected for the future. This will include a view on 1. the general importance of Gennany as a market for goods sold online, 2. an examination oft he demand side as well as the supply side of E-commerce transactions, and 3. of the differences that exist between Germany and other European countries and especially between Germany and the United States.
Keywords: 650